Diseño e implementación de un sistema para la generación eléctrica basado en celdas bioenergéticas aplicado a una red de sensores - Allauca Carrillo, Kleber Eduardo (2021)
The objective of this research was to design and construct bioenergy cells using organic matter mixed with different types of soil such as black, saline, sandy and from the banks of the Chibunga River in the city of Riobamba to generate energy and feed a network of sensors. For the construction of the cells, plastic containers and copper, stainless steel and coated aluminum metals were used for the electrodes, in addition to granular activated carbon previously crushed with NPK (chemical fertilizer) to improve the generation of energy. Twelve cells were constructed with the different types of soil and metals for the electrodes; the cells were monitored in real time for seven days and the voltages generated were measured every 10 minutes. As a result, it was determined that the cell constructed with black soil and steel electrode was the most efficient, which was replicated for use as a feeder for a sensor network.